2008
DOI: 10.1074/jbc.m800613200
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of the Dengue Virus Type 2 NS5 Methyltransferase Domain

Abstract: The Flavivirus NS5 protein possesses both (guanine-N7)-methyltransferase and nucleoside-2 -O methyltransferase activities required for sequential methylation of the cap structure present at the 5 end of the Flavivirus RNA genome. Seventeen mutations were introduced into the dengue virus type 2 NS5 methyltransferase domain, targeting amino acids either predicted to be directly involved in S-adenosyl-L-methionine binding or important for NS5 conformation and/or charged interactions. The effects of the mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 53 publications
4
64
0
1
Order By: Relevance
“…The sequence alignment of the D2MT domain that was substituted with D4MT ( Fig. 1A) shows that all of these amino acid residues that were shown to be important for N-7 and 2Ј-OMe activities and viral replication (49) are conserved in the D2MT and D4MT domains. This observation may explain why the MT activities were not affected ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence alignment of the D2MT domain that was substituted with D4MT ( Fig. 1A) shows that all of these amino acid residues that were shown to be important for N-7 and 2Ј-OMe activities and viral replication (49) are conserved in the D2MT and D4MT domains. This observation may explain why the MT activities were not affected ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the clustered mutations targeting the S-adenosylmethionine binding pocket (K76A/D79A and G81A/G83A/G85A) or the mutation of MT active site residues (D146A/E149A) all either abolished or severely reduced both N-7 and 2Ј-OMe activities (Ͼ90%). Interestingly, the S46A and D131A mutations were unstable and reverted back to WT (49). The sequence alignment of the D2MT domain that was substituted with D4MT ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The wild-type and mutant plasmids were used to produce in vitro RNA transcripts as described previously (13). The in vitro transcripts were transfected into BHK-21 cells to recover infectious virus, and the virus was analyzed for the presence of the introduced mutation as described previously (14).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have established functional significance of conserved residues within the AdoMet-binding pocket (19,20,28,37). Those studies showed that mutations of residues predicted to be involved in AdoMet binding (such as Ser-56, Gly-81, Gly-83, Gly-85, Trp-87, Lys-105, His-110, Glu-111, Asp-131, Ile-147, Asp-146, and Glu-149) reduced, and in some cases abolished, either the N7 or the 2Ј-O-methylation, or both.…”
Section: Structural Comparison Between the Mtase⅐sin And Mtase⅐adohcymentioning
confidence: 99%
“…The differences between host and viral cap formation could potentially be used for development of antiviral therapy. Flavivirus MTase has been shown to be essential for WNV (20,27), Kunjin virus (35), YFV (36), and DENV replication (37). Furthermore, sinefungin (SIN), an AdoMet analog, was shown to inhibit both N7 and 2Ј-O-methylations of WNV MTase, as well as to inhibit WNV replication in cell culture (28).…”
mentioning
confidence: 99%